Fracture union in extra articular distal tibia fracture after definitive delta frame external fixation in COVID 19 pandemic: a case report - Mahajan, Neetin P.; G.S., Prasanna Kumar; Patil, Tushar Chandrakant; Bagimani, Pramod K. (International Journal of Research in Orthopaedics, 2021)
Distal tibia fractures account for 10% of lower limb fractures. Mode of trauma also determines the fate of soft tissue recovery. In low energy fractures soft tissue show better healing whereas fractures due to high energy trauma show high chances of soft tissue complications like poor soft tissue coverage, wound infection and necrosis. We presented a 50 years old male case of extra articular left distal tibia fibula open fracture managed by delta frame external fixator with fibular K wiring used as a definitive management with good fracture healing and range of motion 5 months postoperative. Ankle spanning external fixation is a good modality of surgical management of extra articular compound distal tibia fractures as both temporary and definitive surgical fixation.